HUBUNGAN DURASI METODE KANGURU DENGAN KEBERHASILAN PEMBERIAN ASI PENUH PADA BLLR - , Tri Tunggal; , Prof. dr. Mohammad Hakimi, Ph.D., Sp.OG(K) ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Kangaroo method which is a skin direct contact between mother and her baby can increase administration of breastmilk. This kind of care is done to maximize the stability of infant condition because this is considered more efficient, easy to perform, cheap and safe for both the mother and her baby. The quality of this method lies in its natural heat source effective to maintain body normal temperature for the contact results in the natural heat that can warm up the baby continuously when the mother can breastfeed the baby as much as she wishes to. Eventually, frequent sucking on the motherâs nipple will stimulate the secretion of breastmilk. Kangaroo method kown relationship duration with the success of full breastfeeding in udy was aimed to find out effectiveness of long term use of kangaroo method in Low Birth Weight (LBW). The study subjects were newborns with 2000- 2499 gram in weight treated in Perinatology room of Ulin Banjarmasin Local Hospital who received kangaroo method, after the baby condition was stable. The subjects had met inclusion and exclusion criteria in the period of October 2010 to February 2011. The sample size was 135 pairs of mothers and LBW babies. Data analysis used chi-square statistical test and multivariate analysis using logistic regression. Babies who received kangaroo method enough duration increased breastfeeding to 2.08 times greater significantly. In addition, the result of multivariate analysis showed significance between kangaroo method with a short duration and breastfeeding in LBW babies with OR : 6.08, CI 95% : 2.4-15.2, adjusted R2 0.29. Implementation of kangaroo method enough duration increased breastfeeding to 2 times greater compared to babies who received kangaroo method short duration.